TV Assembleia de Minas Gerais: uma análise a partir do conceito de accountability à luz da teoria democrática contemporânea - Mascarenhas, Rodrigo Élcio Marcelo (2019)
Legislative televisions appeared in Brazil in 1995 with the objective of transmitting all the plenary meetings of the Legislative Houses of the Country, live and without cuts. After 23 years of existence, some of them, such as TV Senado, TV Câmara and TV Assembleia of Minas Gerais, have concession of radio broadcast signal and produce their own programming for 24 hours a day. In this scenario, this research investigates, in the case of TV Assembleia de Minas Gerais, the performance of the broadcaster based on the concept of accountability in light of contemporary democratic theory. For this, a study of democratic theory is carried out in an elitist, pluralist, participatory and deliberative perspective, according to which the search for democratic deepening is extracted through the adoption of deliberation tools in Public Administration, as well as through the use of so-called participatory institutions (IPs). In addition, the concept of accountability provides the research with subsidies for an analysis based on the need for instruments and mechanisms to be accountable, transparency, quality management and punishment of public agents. In relation to publicly funded broadcasters, accountability requires efficient and transparent self-regulation. With this, the research analyzes the legal framework applicable to the legislative televisions and the scenario of deliberation, participation and accountability in the TV Assembleia of Minas Gerais, based on documentary, normative data and a questionnaire applied to the journalist of the broadcaster. The result of the research suggests non-existent self-regulation, in addition to low influence of the citizens in the action of the legislative channel.